2005
DOI: 10.1016/j.febslet.2004.12.077
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the activity of recombinant rat skeletal muscle cytosolic sialidase

Abstract: Rat cytosolic sialidase is expressed at elevated levels in skeletal muscle and is believed to play a role in the myogenic differentiation of muscle cells. Here, we observed varying levels of enhancement of sialidase activity in the presence a range of divalent cations. In particular, a significant enhancement of activity was observed in the presence of Ca 2+ . Conversely, inhibition of the sialidase activity was found when the enzyme was incubated in the presence of Cu 2+ , EDTA, and a range of carbohydrate-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…In agreement with the results obtained for a purified rat liver cytosolic sialidase, 17 adding Cu 2+ (10 mM) significantly decreased the activity of NEU2 to 5%. It is interesting to note that these observations are different from a partially purified recombinant rat cytosolic sialidase whose activity was stimulated by the presence of a divalent cation such as Ca 2+ , Mn 2+ , or Mg 2+ 19. …”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…In agreement with the results obtained for a purified rat liver cytosolic sialidase, 17 adding Cu 2+ (10 mM) significantly decreased the activity of NEU2 to 5%. It is interesting to note that these observations are different from a partially purified recombinant rat cytosolic sialidase whose activity was stimulated by the presence of a divalent cation such as Ca 2+ , Mn 2+ , or Mg 2+ 19. …”
Section: Resultsmentioning
confidence: 75%
“…10,17,18 Plasma membrane NEU3 is believed to be more specific towards gangliosides except for GM1 and GM2. 12,1921 Similar to NEU2, membrane-associated NEU4 has activity against a broad range of sialylglycoconjugates. 22,23 …”
Section: Introductionmentioning
confidence: 99%
“…Itzstein et al reported that hNeu2 require calcium ion for their NA activity, and the NA activity decreases by one-half by the addition of 7 mM copper salt. 28 As shown in Figure 3a, the NA activity of hNeu2 disappeared in the presence of a copper salt even at a very low copper concentration (50 μM CuSO 4 ) in the presence of 4 mM calcium salt. To negate the effect of the copper salt, the effect of a chelating agent for the copper ion, 2-({2-[bis(carboxymethyl)amino]ethyl}(carboxymethyl)amino) acetic acid (EDTA) was evaluated.…”
Section: First Screening Of the Focused Library 3 Prepared By The CLImentioning
confidence: 79%
“…To negate the effect of the copper salt, the effect of a chelating agent for the copper ion, 2-({2-[bis(carboxymethyl)amino]ethyl}(carboxymethyl)amino) acetic acid (EDTA) was evaluated. Although Itzstein et al reported that 1 mM EDTA also decreased the NA activity of hNeu2 by half, 28 addition of 1 equivalent of EDTA recovered the NA activity of hNeu2 completely, and a small excess of EDTA did not affect the activity ( Figure 3). The reported inhibition effect in the presence of 1 mM EDTA might be due to the absence of external addition of calcium ion.…”
Section: First Screening Of the Focused Library 3 Prepared By The CLImentioning
confidence: 86%
See 1 more Smart Citation